A self-controlled comparative clinical trial to explore the effectiveness of three topical hemostatic agents for stopping severe epistaxis in pediatrics with inherited coagulopathies. Issue 6 (September 2014) - Eshghi, P.; Jenabzade, A.; Habibpanah, B.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective The aim of this study was to assess the effectiveness of localized treatments to persistently stop epistaxis in patients with inherited bleeding disorders. Methods In a self-controlled comparative clinical trial, to offer the best solution to stop epistaxis at home (within 10 minutes), patients with inherited bleeding disorders were treated using three different topical hemostatic agents, including Tranexamic acid impregnated tampon, EpiCell tampon prepared from oxidized regenerated cellulose pad, and ChitoHem tampon (reinforced with chitosan). The results of using these different products on three groups of randomly selected patients were ultimately compared using the χ2 and Fisher's exact test statistics. Results A total of 31 patients, 5 females and 26 males with a mean age of 5.6 years, were included in the study. Twenty-three patients had Glanzmann disease, four had von-Willebrand disease, two had Bernard soulier syndrome, two had activated factor VII deficiency, and one patient had impaired secretion of adenosine deaminase. The study exhibited that statistically there was no significant difference between EpiCell tampon and Tranexamic acid impregnated tampon treatments with respect to the hemostasis duration. However, ChitoHem tampon was more efficient than Tranexamic acid impregnated tampon (P value <0.001) and EpiCell tampon (P value < 0.05). Conclusion ChitoHem tampon, the chitosan-reinforced product, was the best therapy solution to stop epistaxis. We recommend further research on the use of other hemostatic agents for localized bleeding in patients with inherited bleeding disorders.